PENGUATAN LITERASI BIBLIKA PERJANJIAN LAMA MELALUI KULIAH UMUM BAGI MAHASISWA TEOLOGI DI STFT JAFFRAY MAKASSAR - Gernaida Krisna R. Pakpahan; Robi Panggara (Penerbit Widina, Widina Media Utama, 2026)
This community service program aimed to strengthen Old Testament biblical literacy among theology students at STFT Jaffray Makassar through an academic public lecture focusing on how Old Testament prophets embodied the prophetic voice. The program was grounded in the need to help students read the prophetic books not merely as collections of predictions or historical texts, but as theological witnesses that shape faith reasoning, ministerial integrity, ethical courage, social sensitivity, and communal hope. The activity employed an educative-participatory approach implemented through three stages: preparation, public lecture delivery, and evaluation with follow-up planning. The program was attended by 86 participants, consisting of undergraduate theology students, postgraduate students, lecturers, and academic staff. Of these participants, 79 evaluation responses were eligible for analysis. The evaluation results indicated that the activity was rated very good, with an overall mean score of 4.67 or 93.32%. The highest score was obtained in the speaker’s mastery of the subject, with a score of 4.82, followed by topic relevance at 4.71, academic benefit at 4.68, clarity of material at 4.63, and quality of interaction at 4.49. The findings show that a public lecture can serve as an effective academic community service model for strengthening students’ understanding of the prophetic voice as a praxis of faith that integrates the word of God, social critique, liturgical renewal, and the contemporary responsibility of church ministry. ABSTRAKKegiatan Pengabdian kepada Masyarakat ini bertujuan memperkuat literasi Biblika Perjanjian Lama mahasiswa teologi di STFT Jaffray Makassar melalui kuliah umum akademik yang berfokus pada bagaimana para nabi Perjanjian Lama menghidupi suara kenabian. Kegiatan ini dilatarbelakangi oleh kebutuhan mahasiswa untuk membaca kitab-kitab nabi tidak hanya sebagai kumpulan nubuat atau teks historis, tetapi sebagai kesaksian teologis yang membentuk nalar iman, integritas pelayanan, keberanian etis, kepekaan sosial, dan pengharapan umat. Metode pelaksanaan menggunakan pendekatan edukatif-partisipatif melalui tiga tahap, yaitu persiapan, pelaksanaan kuliah umum, serta evaluasi dan tindak lanjut. Kegiatan diikuti oleh 86 peserta yang terdiri atas mahasiswa S1 Teologi, mahasiswa pascasarjana, dosen, dan tenaga kependidikan. Dari jumlah tersebut, 79 respons peserta layak dianalisis. Hasil evaluasi menunjukkan bahwa kegiatan berada pada kategori sangat baik, dengan rata-rata keseluruhan 4,67 atau 93,32%. Aspek penguasaan narasumber memperoleh skor tertinggi, yaitu 4,82, diikuti relevansi topik 4,71, manfaat akademik 4,68, kejelasan materi 4,63, dan kualitas interaksi 4,49. Hasil kegiatan menunjukkan bahwa kuliah umum efektif sebagai media PkM akademik dalam memperkuat pemahaman mahasiswa mengenai suara kenabian sebagai praksis iman yang menghubungkan firman Allah, kritik sosial, pembaruan ibadah, dan tanggung jawab pelayanan gereja masa kini.